ORGANIZATIONAL DYNAMICS AND PUBLIC PARTICIPATION IN KENYA: A CRITICAL LITERATURE REVIEW - Wairimu, Linnet (American Journal of Public Relations, 2022)
Purpose: Organizational dynamics entails structural behavior which may include how employees are organized, how daily work deliverables are executed and how the resources are expended. Lack of public participation in CDF-funded projects commonly leads to failure or delay in completion of these projects. Our purpose of study therefore is to evaluate the influence of organizational dynamics on public participation practices in Constituency Development Fund (CDF) funded projects in Kenya, with reference to Manyatta Constituency in Embu County. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concluded that financial audit committees of CDF projects must be competently trained and imparted with relevant financial management skills and that they should be able to operate independently where they frequently hold quality meetings without undue pressures from any unwarranted quarters. The study also made the conclusion that project leadership, financial resources, and staff training played a critical role in influencing public participation in CDF projects. Unique Contribution to Theory and Practice: The study recommends that, all CDF managers should be compelled by the public to allow and embrace public participation as an integral part of management of CDF funded projects. There must be proper priority setting in initiation of CDF funded projects to foster prudent financial resources management by CDF committees. This will further enhance proper running of all activities associated with CDF such as public participation which is a requirement by law